2019
DOI: 10.1590/0037-8682-0405-2018
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of relative handgrip strength and cardiometabolic risk in individuals with HIV/AIDS

Abstract: Introduction: Low handgrip strength (HS) is associated with cardiometabolic alterations that have affected people with HIV/ AIDS. Methods: This was a cross-sectional study performed in adults receiving antiretroviral treatment. HS was evaluated using a dynamometer and divided by body weight to obtain the relative strength. The association between relative HS and overweight, increased waist circumference (WC), high body fat percentage, glycemia, and lipid ratios were assessed using logistic regression. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
2
2
0
Order By: Relevance
“…18,34 In the present study, two pathways related to the understanding of HGS with body composition were verified: the first shows that the greater the lean mass, the greater the HGS; the second points to an inversely proportional principle, in which the greater the values of BMI, abdominal circumference, sum of skinfolds, percentage of fat, and fat mass, the lower the HGS. This response pattern is not limited to body composition; biochemical indicators such as total cholesterol, when altered, are also related to a lower HGS, as seen in the present study and confirmed by Santos et al 15 Thus, as muscle strength is an important component of health-related physical fitness, changes in body composition that reduce muscle strength directly impact the performance of activities of daily living and the functional capacity of people living with HIV. 4,35 Physical exercise programs for people living with HIV are important strategies to improve strength and muscle mass, which are negatively affected by both HIVand the use of antiretrovirals.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…18,34 In the present study, two pathways related to the understanding of HGS with body composition were verified: the first shows that the greater the lean mass, the greater the HGS; the second points to an inversely proportional principle, in which the greater the values of BMI, abdominal circumference, sum of skinfolds, percentage of fat, and fat mass, the lower the HGS. This response pattern is not limited to body composition; biochemical indicators such as total cholesterol, when altered, are also related to a lower HGS, as seen in the present study and confirmed by Santos et al 15 Thus, as muscle strength is an important component of health-related physical fitness, changes in body composition that reduce muscle strength directly impact the performance of activities of daily living and the functional capacity of people living with HIV. 4,35 Physical exercise programs for people living with HIV are important strategies to improve strength and muscle mass, which are negatively affected by both HIVand the use of antiretrovirals.…”
Section: Discussionsupporting
confidence: 89%
“…This response pattern is not limited to body composition; biochemical indicators such as total cholesterol, when altered, are also related to a lower HGS, as seen in the present study and confirmed by Santos et al 15 Thus, as muscle strength is an important component of health-related physical fitness, changes in body composition that reduce muscle strength directly impact the performance of activities of daily living and the functional capacity of people living with HIV. 4,35…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This finding is in line with that obtained in the above-mentioned study, suggesting that HIV infection plays a role in promoting dynapenia in untreated patients. Likewise, it should be considered that men and women may react differently to HIV infection and ART use, so women may have less muscle strength than men (45), as found in a previous study (37). Our analyzes were not stratified by gender, as only 19.5% of our sample consisted of women.…”
Section: Discussionmentioning
confidence: 85%